Early- and middle-stage fluted stone tool bases found near Fox Lake, Wayne County Ohio: Clovis or not?. (June 2019) - Norris, James D.; Stephens, Charles; Eren, Metin I.
Abstract: Goodson Rockshelter in Oklahoma has provided strong chronometric and typological evidence that early- and middle-stage fluted stone tool bases found there date to the Late Archaic. These results indicate that such specimens are not necessarily diagnostic of the late Pleistocene Clovis culture. Here, we present additional evidence that early- and middle-stage fluted bases do not automatically indicate a Clovis presence. The lithic assemblages east of the Fox Lake area in Northeast Ohio consist of debitage and tools, including five early- and middle-stage fluted bifaces. However, of the 20 diagnostic projectile points found in the surrounding area, all can be assigned to the Holocene (Early Archaic to the Late Prehistoric), and none to the Pleistocene. Until chronometric assessments of age can be conducted, the most parsimonious explanation for this pattern is that these early- and middle-stage fluted bifaces east of Fox Lake are Holocene in age, and not affiliated with the Clovis culture. Graphical abstract: Unlabelled Image Highlights: Early- and middle-stage fluted bifaces are assumed to be Clovis. Evidence from Goodson Rockshelter, Oklahoma, questioned this assumption. Evidence from Fox Lake, Ohio, further questions this assumption.